Profiling nucleotides in low numbers of mammalian cells by sheathless CE–MS in positive ion mode: Circumventing corona discharge. Issue 5 (13th January 2020) - Zhang, Wei; Guled, Faisa; Hankemeier, Thomas; Ramautar, Rawi
Abstract: Negative ion mode nano‐ESI–MS is often considered for the analysis of acidic compounds, including nucleotides. However, under high aqueous separation conditions, corona discharge is frequently observed at emitter tips, which may result in low ion abundances and reduced nano‐ESI needle emitter lifetimes. In this work, we introduce a sheathless CE‐MS method for the highly efficient and sensitive analysis of nucleotides employing ESI in positive ion mode, thereby fully circumventing corona discharge. By using a background electrolyte of 16 mM ammonium acetate (pH 9.7) a mixture of 12 nucleotides, composed of mono‐, di‐, and tri‐phosphates, could be efficiently analyzed with plate numbers per meter above 220 000 and with LODs in the range from 0.06 to 1.3 nM, corresponding to 0.4 to 8.6 attomole, when using an injection volume of about 6.5 nL only. The utility of the method was demonstrated for the profiling of nucleotides in low numbers of mammalian cells using HepG2 cells as a model system. Endogenous nucleotides could be efficiently analyzed in extracts from 50 000 down to 500 HepG2 cells only. Moreover, apart from nucleotides, also some nicotinamide‐adenine dinucleotides and amino acids could be analyzed under these conditions, thereby clearly illustrating the utility of this approach for metabolic profiling of low amounts of biological material.